Social anxiety in preadolescents: Intervention program - Robles Ridi, Pamela (2018)
The objective of this study was to evaluate Social Anxiety in preadolescents of an educational establishment in the Province of San Luis, Argentina, and then intervene through a workshop through three stages: Pre-Intervention, Post-Intervention and Follow-up. The Horse Social Anxiety Questionnaire, Arias Salazar, Irurtia and Ollendick (CASO-N24, 2012) was administered. The sample consisted of 13 preadolescents, of both sexes, whose ages were between 10 and 11 years. The analysis was carried out by means of a longitudinal study of repeated measures. The results show significant differences after the intervention performed. This indicates effectiveness in the intervention carried out, favoring the reduction of Social Anxiety in an evolutionary stage of great vulnerability.